ASPEK PERLINDUNGAN HUKUM BAGI PELAKU USAHA TERHADAP KONSUMEN BERITIKAD BURUK DALAM TRANSAKSI DIGITAL - Ghozel Indrawan; Abid Assidiqi Zahra (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The rapid development of digital transactions has facilitated interactions between businesses and consumers, but it also poses the risk of bad faith consumers. Bad faith consumers are those who intentionally exploit digital systems to harm businesses, through actions such as identity fraud, misuse of return mechanisms, or manipulation of product reviews and ratings. This phenomenon demands adequate legal protection to prevent businesses from experiencing financial or reputational losses. This article analyzes aspects of legal protection for businesses in digital transactions in Indonesia, based on Law Number 8 of 1999 concerning Consumer Protection, Law Number 11 of 2008 concerning Electronic Information and Transactions and its amendments, and provisions in the Civil Code concerning contracts and defaults. Protection strategies discussed include consumer identity verification, the development of clear transaction terms and conditions, the use of digital contracts, and the implementation of transaction security and monitoring systems. Law enforcement challenges, such as easily manipulated electronic evidence and slow legal procedures, are also examined. In conclusion, a combination of legal protection and technology-based preventive measures is key for businesses to conduct digital transactions safely, effectively, and sustainably.